Physical abuse of domestic maids - an analysis of the extent to which local laws protect these workers / Noor Aishah KM Abu Bakar, Zetty Shahfrina Abd Rahman and Siti Nor Asmah Mohd Noor Nordin - KM Abu Bakar, Noor Aishah; Abd Rahman, Zetty Shahfrina; Mohd Noor Nordin, Siti Nor Asmah (2006)
The title of our project paper is "The Physical Abuse of Domestic Maids - An Analysis of The Extent to Which Local Laws Protect These Maids". In Chapter One, we provided the history, background study of the entry of the Indonesian domestic maids to Malaysia and we mentioned the objectives and scope of our study. The significance and the limitations of study are also included in this chapter. In Chapter Two, we have used several articles written by various authors for the literature review. From our observation, we have found that most of the authors wrote about abuse in general. Also, they did not give their recommendations in solving the matter. In the Third Chapter, we decided to do an analysis on the related issues of the physical abuse against domestic maids. In this chapter, we gave an overview definition of domestic maids and the proximate number of maids working in Malaysia. Indonesia has the highest number of domestic maids working in Malaysia and the worst protection of rights among other countries. In Chapter Four, we focused on the issue of physical abuse of these domestic maids and the feedback from Malaysia and Indonesia to solve the issue. In Chapter Five, we did an overview of the law and rights of the domestic workers in Malaysia and we mentioned about the rights that these domestic maids should get. In the Last Chapter, we have provided the recommendations to solve this issue.